Analisis Penerapan Manajemen Strategik dan Pengaruhnya terhadap Kinerja Usaha - Mutinda Teguh Widayanto (Universitas Islam Kadiri, 2020)
This research was conducted to determine the degree of implementation of Strategic Management and the level of MSME (Miicro. Small, and Medium Enterprise) business performance in the Batik, Craft and Furniture sector in Probolinggo District, East Java and to examine the relationship between Strategic Management Application and Business Performance. The population of this research is the MSMEs of the Batik, Craft and Furniture sectors in Probolinggo District with a purposive sampling method, and those who meet the requirements of 30 samples. The method used is a survey through a questionnaire to find out primary data of degrees in the Implementation of Strategic Management and secondary data on business performance. To test the relationship between variables, a statistical test was carried out using the linear regression method with the SPSS tool. The results showed that the degree of implementation of Strategic Management and Business Performance of respondents was included in the medium category. Statistical test results show that there is a positive and significant effect of the Implementation of Strategic Management on Business Performance. The results of this study should be input for stakeholders in an effort to improve the competence of MSMEs in dealing with business competition.